2011
DOI: 10.1002/ajp.20972
|View full text |Cite
|
Sign up to set email alerts
|

Within‐group social bonds in white‐faced saki monkeys (Pithecia pithecia) display male–female pair preference

Abstract: White-faced saki monkeys (Pithecia pithecia) lack most of the behavioral and physical traits typical of primate monogamy [Fuentes, 1999]. In order to determine if social bonds in this species reflect patterns displayed by pair-bonded groups or larger multimale-multifemale groups, we draw on 17 months of data collected on wild white-faced sakis at Brownsberg Nature Park, Suriname. We analyzed within-group social bonds for three habituated groups (one two-adult and two multiadult groups) by measuring grooming, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…For example, our examination of 12 years of data on group composition and demography for six social groups of sakis indicated that during 45% of group‐months, groups contained two or more adult females and/or two or more adult males (Van Belle, Fernandez‐Duque, & Di Fiore, ). That is, groups of equatorial sakis were often not “pair‐living,” an observation that is consistent with observations for other pitheciines (Thompson, ; Thompson & Norconk, ). Moreover, we have also documented several cases when more than one adult female (including mother‐daughter pairs) reproduced in the same group at the same time, belying characterization of P. aequatorialis as either sexually or genetically monogamous.…”
Section: Our Research Program On “Monogamy” In Wild Platyrrhinessupporting
confidence: 84%
“…For example, our examination of 12 years of data on group composition and demography for six social groups of sakis indicated that during 45% of group‐months, groups contained two or more adult females and/or two or more adult males (Van Belle, Fernandez‐Duque, & Di Fiore, ). That is, groups of equatorial sakis were often not “pair‐living,” an observation that is consistent with observations for other pitheciines (Thompson, ; Thompson & Norconk, ). Moreover, we have also documented several cases when more than one adult female (including mother‐daughter pairs) reproduced in the same group at the same time, belying characterization of P. aequatorialis as either sexually or genetically monogamous.…”
Section: Our Research Program On “Monogamy” In Wild Platyrrhinessupporting
confidence: 84%
“…Together, these observations suggest a more flexible grouping pattern for this species than previously presumed. Our observations are in line with grouping patterns reported for P. pithecia living in pristine forest at Brownsberg Nature Park, Suriname, where multi-year observations have revealed that two-adult groups may gradually accumulate offspring over time as some offspring have been observed to mate in their natal group or inherit the home range of their parents [Thompson & Norconk, 2011]. Our findings suggest that a variable grouping pattern is not restricted to P. pithecia alone, but might also be characteristic of Amazonian sakis.…”
Section: Discussionsupporting
confidence: 89%
“…This has been reported in small primates such as titis monkeys (Callicebus discolor: de Luna et al, 2010) and saki monkeys (Thompson & Norconk, 2011), as well as in white-handed gibbons (Hylobates lar: Reichard, 2003) and siamangs (Symphalangus syndactylus: Lappan, 2008). In our study area, gibbon infants face predation from eagles (Spilornis cheela) (personal observation), and obviously dependent offspring (InR) would most likely require protection.…”
Section: Discussionsupporting
confidence: 69%
“…Even among young gibbons, individuals also maintained proximity with individuals of the same matrilineal line. When the dependent offspring grew older, the proximity between mother and offspring declined, as observed in saki monkeys (Pithecia pithecia: Thompson & Norconk, 2011).…”
Section: Discussionmentioning
confidence: 91%